ChemInform Abstract: Synthesis of Bis‐spiro Cyclopropanes Based on Meldrum′s Acid by Milling. Issue 32 (August 2015) - Kashani, Elmira; Noroozi Pesyan, Nader; Tunc, Tuncay; Sahin, Ertan
Abstract Reaction of Meldrum′s acid with various solid aldehydes in the presence of cyanogen bromide and solid sodium ethoxide leads to the selective and efficient formation of bis‐spiro cyclopropanes (III) under mild conditions.